Core decompression isolated or combined with bone marrow-derived cell therapies for femoral head osteonecrosis. (4th March 2021) - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Jörg; Tingart, Markus; Baroncini, Alice
ABSTRACT: Objectives : The regenerative capabilities of bone marrow-derived cell therapies (BMCTs) have been employed in combination with core decompression (CD) in the management of osteonecrosis of the femoral head to prevent or delay the necessity of total hip arthroplasty (THA). Methods : The authors conducted a meta-analysis to compare the results of level of evidence I trials comparing CD with and without BMCTs. Results : Overall, 579 procedures were analyzed: 265 in the CD group and 263 in the CD + BMCTs group. Comparability concerning age and gender, drill size, etiology, and grade of OFNH was found (P > 0.1). At a mean follow up of 82.29 (24 to 360) months, the VAS scored favourably for the CD + BMCTs group (mean difference: −12.88; P < 0.0001), as well the rate of THA (odd ratio: −0.14; P < 0.0001). Time to failure (P = 0.4) and to THA (P = 0.9) was similar between the two groups, as was the rate of failure (P = 0.3). Conclusion : In patients with femoral head osteonecrosis, core decompression combined with BMCTs demonstrated reduced pain and lower rate of total hip arthroplasty compared to core decompression as an isolated procedure.